Carbon‐Nitride Popcorn—A Novel Catalyst Prepared by Self‐Propagating Combustion of Nitrogen‐Rich Triazenes. Issue 12 (13th January 2023) - Ma, Jinchao; Das, Jagadish; Zhang, Jiaheng; Cheng, Jian; Sorcar, Saurav; Rosen, Brian A.; Shekhter, Pini; Dobrovetsky, Roman; Flaxer, Eli; Yavor, Yinon; Shen, Ruiqi; Kaminker, Ilia; et al.
Abstract: The interest in development of non‐graphitic polymeric carbon nitrides (PCNs), with various C‐to‐N ratios, having tunable electronic, optical, and chemical properties is rapidly increasing. Here the first self‐propagating combustion synthesis methodology for the facile preparation of novel porous PCN materials (PCN3‐PCN7) using new nitrogen‐rich triazene‐based precursors is reported. This methodology is found to be highly precursor dependent, where variations in the terminal functional groups in the newly designed precursors (compounds 3–7) lead to different combustion behaviors, and morphologies of the resulted PCNs. The foam‐type highly porous PCN5, generated from self‐propagating combustion of 5 is comprehensively characterized and shows a C‐to‐N ratio of 0.67 (C3 N4.45 ). Thermal analyses of PCN5 formulations with ammonium perchlorate (AP) reveal that PCN5 has an excellent catalytic activity in the thermal decomposition of AP. This catalytic activity of PCN5 is further evaluated in a closer‐to‐application scenario, showing an increase of 18% in the burn rate of AP‐Al‐HTPB (with 2 wt% of PCN5) solid composite propellant. The newly developed template‐ and additive‐free self‐propagating combustion synthetic methodology using specially designed nitrogen‐rich precursors should provide a novel platform for the preparation of non‐graphitic PCNs with a variety of building block chemistries, morphologies, and properties suitable for a broad range of technologies. Abstract : Novel nitrogen‐rich triazene precursors are synthesized and used for preparation of non‐graphitic carbon nitrides (PCNs). The molecular structures of these precursors define their self‐propagating combustion behavior, morphology, and properties of the resulting PCNs. One of the obtained PCNs is found to function as a catalyst for ammonium perchlorate decomposition and burn rate modifier of a solid AP‐Al‐HTPB composite rocket propellant.